VOLATILITY IN CRUDE OIL PRICES AND SECTORAL PERFORMANCE: AN ANALYTICAL STUDY - Martinez, Ana; Schmidt , Oliver; Thompson, Isabella (Ayden International Journal of Banking, Finance and Technology, 2024)
The study investigated the impact of crude oil price fluctuations on selected economic sectors in Nigeria from 1986 to 2021. The data for the study, sourced from the Central Bank of Nigeria statistical Bulletin of various volumes, was analysed using Autoregressive Distributed Lag (ARDL) approach. The study focused on the Agricultural, Information and Communication and Manufacturing sectors of the Nigeria economy. The results of the analysis showed that a long–run relationship existed between crude oil price fluctuations and the sampled sectors’ returns. Specifically, the study found that crude oil price fluctuations had a negative and significant effect on agricultural and telecommunication sector in the long-run, while its effect on the manufacturing sector was positive and statistically significant at 5% level. Hence, it was recommended among other things that Nigeria should diversify her export revenue base as a means of minimizing reliance on crude oil and petroleum products